Height of the Medial Longitudinal Arch During Classical Ballet Steps - de Mello Viero, C.C.; Kessler, L.P.; Pinto, C.; Gontijo, K.N.S.; da Rosa, RG; Kleiner, A.; Peyré-Tartaruga, LA; do Pinho, A.S.; de Souza Pagnussat, A. (Journal of dance medicine & science : official publication of the International Association for Dance Medicine & Science, 2017)
n/a
cited By 3